RC slabs strengthened with externally bonded CFRP strips under long-term environmental exposure and sustained loading. Part 2: Laboratory experiments - Matteo Breveglieri (Elsevier, 2021)
This investigation consists of two parts (outdoor and laboratory experiments). The first part described RC slabs strengthened with prestressed and non-prestressed CFRP strips; these slabs were loaded and exposed to an outdoor environment for four years. It was found that the elevated temperatures reached in the adhesive did not significantly affect the service behaviour of non-prestressed EB CFRPs, but could lead to the failure of the prestressed system.In the second part of the discussion, laboratory experiments are presented. Failure tests were performed to determine the ultimate strengths of the slabs. The results demonstrate that long-term exposure (thermal cycles and sustained load) does not affect the load-carrying capacity of the strengthened RC elements. Furthermore, an additional slab with an identical strengthening configuration was tested after being subjected to thermal cycles under a heavy sustained load under laboratory conditions, allowing us to better understand and verify the results obtained during the long-term experiments.